Review and future trend of energy harvesting methods for portable medical devices - Paulo, J. (2019)
Submitted by GASPAR (dinis@ubi.pt) on 2019-10-21T10:41:45Z No. of bitstreams: 1 WCE2010_ICEEE_74_EnergyHarvesting.pdf: 497984 bytes, checksum: 82b3fc5be4a1b9991eef041444cb5687 (MD5)